Fatigue As A Performance Shaping Factor In Human Reliability Analysis For Long-Duration Spaceflight. (December 2020) - Boring, Ronald; Ulrich, Thomas; Mortenson, Torrey; German, David
This paper provides background on the process to enhance human reliability analysis (HRA) for long-duration space applications. While short-duration missions largely mirror ground activities and fit well with existing HRA methods, new missions to the Moon or Mars entail a significantly longer duration of time in space for astronauts. This extended period in space presents opportunities to affect astronaut performance that require consideration of new performance shaping factors (PSFs). In the present paper, we conducted a meta-analysis on fatigue and developed a new PSF to account for chronic sleep deprivation associated with long-duration space missions. Fatigue provides a starting point for additional PSFs needed for space HRA.